Systematic review of sex-based differences in opioid-based effects. (3rd September 2018) - Huhn, Andrew S.; Berry, Meredith S.; Dunn, Kelly E.
Abstract: There are several biological factors that might play a role in physiological response to opioids and/or the onset of problematic opioid use; however, sex-based differences in non-analgesic opioid-based effects are poorly understood. The goal of this review is to provide a current analysis of the pre-clinical literature on sex-based differences in response to endogenous and exogenous opioids, including the interplay between sex hormones and opioid receptor-mediated neuronal activity and associated behaviours. A systematic search was performed on the following terms within PubMed between March and April 2018: 'opioid oestrogen', 'opioid progesterone', 'opioid oestradiol', and 'opioid testosterone'. Pre-clinical research on the non-analgesic, sex-based effects of opioids is disparate, both in terms of methodology and outcomes, which prohibits a cohesive summary of the results. Themes from the pre-clinical literature suggest that opioid receptor binding, coupling, and density vary as a function of hormone exposure. Findings also suggest that interactions between endogenous opioid and stress systems may differ between males and females as a function of ovarian hormones. Given the current opioid-related public health crisis, there is a pressing need to increase systematic pre-clinical and clinical research on sex-based differences in opioid-effects and opioid use disorder.